On some new features of semiannual variation of the geomagnetic field - Bhargava, B.N.; Rao, D.R.K. (My University, 1983)
.
Keywords: Geomagnetic field; Semiannual variation; Magnetic field; Solar terrestrial interactions; Geomagnetism; Equinoxes